Economic and ecological constraints of hybrid systems with Bayesian networks - Toure, Amadou Fousseyni; Sissoko, Abdoulaye; Danioko, Fadaba; Tchoffa, David; El Mhamedi, Abderrahman (Institute of Advanced Engineering and Science, 2025)
To confront climate change and the shortage of fossil fuels, countries are turning to renewable energies, particularly solar energy, which is an abundant, inexhaustible energy with a low environmental impact. In Mali, hydraulic and thermal energy sources are insufficient, and the country has been facing a huge energy crisis in recent years. For this reason, the production of solar energy is a major solution. This work proposes a photovoltaic system coupled to the national distribution network to reduce this energy crisis or even resolve it definitively. A preliminary analysis was carried out to define the technical, economic, and ecological conditions for the construction of a 30 MW solar power plant at three interconnection points of the national distribution network of Mali. The objective of this analysis is to determine the economic and ecological constraints of the proposed hybrid system. For modeling, we used the Bayesian network, and for simulation, the BayesienLab simulation tool was used. The simulation results showed a considerable contribution of these three solar power plants in terms of energy deficits, economic deficits, and climate change.